Hospital training and preparedness of parents and carers in paediatric tracheostomy care: A mixed methods study. (March 2022) - Antoniou, Ioanna; Wray, Jo; Kenny, Michaela; Hewitt, Richard; Hall, Andrew; Cooke, Jo
Abstract: Introduction: Within the UK, the majority of paediatric tracheostomy care is delivered by parents and carers at home. To facilitate this, extensive in-hospital training is delivered by a variety of health care professionals. Our goal was to assess carer perceptions of this process and highlight areas in which we can further improve our service and the training for other hospital providers of paediatric tracheostomy care. Methods: A mixed method approach was adopted. In Phase I, qualitative data from five semi-structured interviews with carers of children with a tracheostomy were thematically analysed and subsequently used to develop a questionnaire. In Phase II, the piloted questionnaire was distributed via telephone, email or post to all eligible caregivers who had been tracheostomy trained at GOSH in the last three years (n = 92). Qualitative and quantitative data were analysed using thematic analysis and descriptive statistics respectively. Results: Thirty-five completed questionnaires were received (38% response rate). Overall participants were highly satisfied with the training provided (mean score 8.42 on a scale of 1 (lowest) to 10 (highest)). Carer identified areas requiring improvement were caregiver education pre-tracheostomy; emergency and complication training; supervision and training post hospital discharge; training schedule; emotional support; and support from community healthcare teams. These findings led to multiple subsequent interventions to further improve the carer training programme including training videos, psychology provision on request and increased community training. Conclusion: Although the evaluation of the service revealed high participant satisfaction in home carer training overall, in-depth analysis of caregivers' experiences indicated common themes in the tracheostomy training service where further support would be beneficial. A carer-centred rather than health professional focus on training needs will allow future attention to be directed to areas of need identified by carers themselves as important to improve the tracheostomy training programme.